Tatak Pilipino [episode no. 63] [videorecording]. ([Quezon City ABS-CBN], 1992)
Summary: A unique display of Pilipino ways and style.
Contents: Bullfight in Manila (5 min.) -- Grace Matthews (5 min.) -- Traje de mestiza (10 min.) -- Johnny Delgado (5 min.) -- Juan Luna paintings (5 min.) -- Ati-atihan sa Aklan (3 min.) -- Sto. Nino images annual exhibit (5 min.) -- Smokey Mountain Singers (10 min.).
Crdits: Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Delgado Johnny; Luna, Juan; Matthews, Grace; Santo Nino -- Exhibitions; Smokey Mountain Singers; Bullfights -- Manila; Clothing and dress; Costume design -- Philippines; Festivals -- Philippines; Idols and images -- Exhibitions; Music; Home economics